CONSTATATIVE STUDY ON THE ASSESSMENT IN THE PHYSICAL EDUCATION DISCIPLINE IN THE SECONDARY EDUCATION CYCLE - A.G. DOBRE; F. GRIGORE (Editura Universitatii Transilvania din Brasov, 2020)
We appreciate that the problem of assessment in the education system is addressed in many specialized studies. Following the analysis of the instructional-educational process and the assessment system in the physical education discipline of the secondary education, in the present study, it was started from the idea that in the success of the students of the primary education cycle, the weight of the personal performances prevails, followed and aided by other evaluation criteria. The purpose of the paper was to establish to what extent the success of the physical education discipline is based on a concrete system of the personal performance of the students.